How do grass species, season and ensiling influence mycotoxin content in forage? - Skladanka, Jiri; Adam, Vojtech; Dolezal, Petr; Nedelnik, Jan; Kizek, Rene; Linduskova, Hana; Mejia, Jhonny Edison Alba; Nawrath, Adam (International journal of environmental research and public health, 2013)
Mycotoxins are secondary metabolites produced by fungal species that have harmful effects on mammals. The aim of this study was to assess the content of mycotoxins in fresh-cut material of selected forage grass species both during and at the end of the growing season. We further assessed mycotoxin content in subsequently produced first-cutting silages with respect to the species used in this study: Lolium perenne (cv. Kentaur), Festulolium pabulare (cv. Felina), Festulolium braunii (cv. Perseus), and mixtures of these species with Festuca rubra (cv. Gondolin) or Poa pratensis (Slezanka). The mycotoxins deoxynivalenol, zearalenone and T-2 toxin were mainly detected in the fresh-cut grass material, while fumonisin and aflatoxin contents were below the detection limits. July and October were the most risky periods for mycotoxins to occur. During the cold temperatures in November and December, the occurrence of mycotoxins in fresh-cut material declined. Although June was a period with low incidence of mycotoxins in green silage, contents of deoxynivalenol and zearalenone in silages from the first cutting exceeded by several times those determined in their biomass collected directly from the field. Moreover, we observed that use of preservatives or inoculants did not prevent mycotoxin production.
Keywords: Mycotoxins; Seasons; potravinářská mikrobiologie; Česká republika; Food Microbiology; Risk Assessment; Czech Republic; Poaceae; mykotoxiny; ELISA; hodnocení rizik; zvířata; Humans; lipnicovité; dobytek; Silage; Enzyme-Linked Immunosorbent Assay; Livestock; siláž; roční období; lidé; Animals